2017
DOI: 10.1177/0004867417717796
|View full text |Cite
|
Sign up to set email alerts
|

What is the current level of mental health service delivery and expenditure on infants, children, adolescents, and young people in Australia?

Abstract: The study provides a benchmark for data-driven service planning to ensure that the mental health needs of infants, children and young people are met. Our results indicate that the youngest age group are underserviced relative to need, even noting infants and children may receive services for behavioural/mental health issues from providers not captured in our study (such as paediatricians). The developmental origins of mental illness underlies the urgency of adequate provision by governments of perinatal, infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…Concerns about child protection were highlighted by parents in this review, which highlights the strengths of early investment in ‘normalising’ support which fosters a sense of safety, within ‘mainstream’ care systems. The importance of investment in broader societal factors (housing, education, safety, addressing stigma) were also highlighted in this review, and these investments are likely to have important returns in terms of both secondary prevention for the parent and primary prevention for the infant [99].…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about child protection were highlighted by parents in this review, which highlights the strengths of early investment in ‘normalising’ support which fosters a sense of safety, within ‘mainstream’ care systems. The importance of investment in broader societal factors (housing, education, safety, addressing stigma) were also highlighted in this review, and these investments are likely to have important returns in terms of both secondary prevention for the parent and primary prevention for the infant [99].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, because of the increased likelihood of stigmatization and discrimination accompanying a mental illness, these families may face greater challenges accessing support. This, in combination with a lack of visibility for early intervention support, may explain why less than one in six children are currently receiving support for emerging mental health issues at any one time (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…4 The study adds to the group's interest in developing models for workforce planning 5 and in quantifying the population effect of exposure to risk factors in childhood on adult mental health. 6 In a previous study, 7 this group showed that the mental health needs of the youngest age groups (0-4 years) are underserved by a factor of ten compared with those of youth (18-24 years).…”
Section: Workforce Planning For Children and Young People's Mental Health Carementioning
confidence: 89%